Design improvements of 12 slot-14 pole hybrid excitation flux switching motor with 1.0 kg permanent magnet for hybrid electric vehicles - Ahmad Mazlan, Nor Adillah (2014)
Flux switching machine (FSMs) is a new class of brushless motor used in the automotive industry and have been developed in recent years. The FSMs can be divided into three groups which are permanent magnet flux switching machine (PMFSM), field excitation flux switching machine (FEFSM) and hybrid excitation flux switching machine (HEFSM). Among these three groups, HEFSM has several attractive features and offers the advantages of robust rotor structure together with variable flux control capabilities. These advantages make this machine more attractive to apply for high-speed motor drive system. This project is a design improvements of 12 slot- 14 pole hybrid excitation flux switching machine (HEFSM) with 1.0 kg permanent magnet (PM) for hybrid electric vehicles(HEVs). The design target of maximum torque is 333Nm, a maximum power of more than 123kW, and a maximum power density of more than 3.5kW/kg. The performance of the proposed machine on the initial design and improvements design are analysed based on 2-D Finite element analysis (FEA). The final results prove that the final design HEFSM is able to keep the maximum torque when compared to the initial design HEFSM.